Caribbean Region. Annual report 2009 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2022)
Presents the results of IICA in the Caribbean Region in 2009 in relation to the state of agriculture and rural life, the implementation of the national technical cooperation agenda, interagency cooperation, horizontal technical cooperation, new opportunities for technical cooperation, and the organized activities